Caracterização de interatividade em museus e centros de ciência a partir de teses brasileiras. - Santos, Livia Aceto Ferraz dos (Universidade Federal de São Carlos, 2019)
Since interactivity has become a widely used tool for communicating scientific concepts and meanings in museums and centers of science, there are discussions about its role, its scope, and its limitations. This research project is a bibliographic study that aims to identify what are the characteristics of interactivity in museums and centers of science discussed in Brazilian academic productions. We selected a corpus of six PhD thesis published between 2006 and 2016, from postgraduate programs in education, science teaching and sociology. We work according to the content analysis of Bardin (2016) with focus on thematic analysis. We identified that interactivity in museums and centers of science is more discussed in the personal and sociocultural contexts than in the physical context, according to Falk and Dierking's (2000) Contextual Model of Learning. The characterization approaches are related with the factors: "visit motivation and expectations", "prior knowledge", "choice and control", " within group social mediation", "mediation by others outside the immediate social group" and "design and exposure to exhibits and programs ".
Keywords: Museu e centro de ciência; Interatividade; Exposição interativa; Educação em museu; Análise de conteúdo; Museum and center of science; Interactivity; Interactive exhibition; Education in museum; Content analysis; CIENCIAS HUMANAS::EDUCACAO